2006
DOI: 10.1177/0731684406055455
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Controlling Particle Distribution in Infusion Molded Composites

Abstract: This article presents results from an experimental investigation in which two grades of aluminatrihydroxide (ATH) particles are added to liquid resin and used in infusion molding experiments. Based on the results, potential key mechanisms controlling resin flow and hence also the final particle distribution are proposed. A pore doublet model is proposed to explain the seemingly random spatial distribution of particle-dense regions within the final material. These dense regions are found within flow channels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 6 publications
4
26
0
Order By: Relevance
“…5b. This is in accordance with results presented in [13] reinforcing that it is important to do a detailed study of the flow in dual scale porosity. To start with, the shapes of the flow fronts from the meso‐scale experiments are determined from the acquired images of the flow simply by image analysis.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…5b. This is in accordance with results presented in [13] reinforcing that it is important to do a detailed study of the flow in dual scale porosity. To start with, the shapes of the flow fronts from the meso‐scale experiments are determined from the acquired images of the flow simply by image analysis.…”
Section: Resultssupporting
confidence: 92%
“…Hence, the particle deposition mechanisms due to the fluid transport in dual scale porous media will here be studied in detail by interpreting the velocity field in a model dual‐scale geometry and thus extending the study presented in Ref. [13]. The major benefit with such dual‐scale geometry is that the velocity field in both scales can be investigated simultaneously and that the same geometry can be used for repetition experiments after being carefully cleaned.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…First the suction velocity is assumed to be uniform along the x-axis, whether this is a correct assumption can only be understood if the physics of the surrounding porous medium is taken into account. A theoretical model for this kind of flow was presented by Griffiths et al [9] leading to a Stokes flow in the pipe similar to the flow given by Equation (5) in the present paper. The flow is however modified by a thin surrounding porous medium described by Darcy's law.…”
Section: Discussionmentioning
confidence: 59%
“…For the case when the applied pressure gradient is stronger than capillary action, the channels between the bundles are first filled and the capillary pressure force fills the fluid in the bundles. In experiments mimicking composites manufacturing it is found that the injection of non-spherical particles together with a liquid resin are strongly filtered by fabrics preventing a homogeneous distribution of the particles in the final product, see Fernberg et al [5] and Nordlund et al [6].…”
Section: Of 22mentioning
confidence: 99%